A Review of the Role of the Gold Rahn Contract in Islamic Banks in Educating and Boosting the Financial Improvement of the Community - Nursania Dasopang; Siti Khadijah Matondang; Gusriandi; Rizka Makhrijan Zebua; Ainun Sarkiyah (Al Urwah : Sharia Economics Journal, 2025)
Islamic banks play an important role in providing Islamic financing through the Rahn Emas product, which offers quick liquidity with gold as collateral through the dual Qardh-Ujrah contract. Literature research using a normative-juridical approach aims to analyze the suitability of the Rahn Emas implementation to the DSN-MUI Fatwa No. 25/2002 and No. 26/2002, optimize the potential for financial literacy education, and synthesize contributions to the financial independence of the community from the perspective of maqasid sharia. The population includes normative sharia documents and secondary literature (1992-2025), with a purposive sample of 25-30 sources focused on the context of BSI KC Padangsidimpuan. Instruments consisting of the DSN-MUI fatwa, OJK regulations, and academic literature were analyzed through qualitative content analysis with source triangulation. The results show formal compliance through the separation of Qardh-Ujrah, but substantial issues in the calculation of ujrah are correlated with the loan amount, potentially resembling riba nasi'ah. Rahn Emas functions as a safety net to increase MSME productivity and financial literacy. The conclusion recommends standardization of real-cost-based ujrah, digital literacy workshops, and transparent accounting to strengthen sharia legitimacy and financial inclusion.